Self-stigma formation process among younger and older Israeli Arabs diagnosed with depression. (27th May 2021) - Abo-Rass, Fareeda; Werner, Perla; Shinan-Altman, Shiri
Abstract: Objectives: Self-stigma is common among persons with depression. Still, studies that examined the process of self-stigma concentrated mostly on younger adults (ages 18–65) with mental illness in general, with a limited number of studies examining older adults with depression. This study was aimed to examine and compare the self-stigma formation process and its relation to self-esteem among younger (ages 18–64) and older Israeli Arabs (age 65+) diagnosed with depression. The study was based on a self-stigma model which defines the self-stigma formation process as composed of three stages: stereotypes awareness, stereotype agreement, and self-concurrence. Method: A total of 160 younger and older Israeli Arabs with depression completed measures of self-stigma formation process, self-esteem, and socio-demographic and health characteristics. Results: The self-stigma formation process was found as a multi-level and progressive model for both younger and older adults, despite that older adults reported significantly higher levels of self-stigma in all stages of the process. Low self-esteem was significantly associated with higher levels of stereotype agreement and self-concurrence in both age groups. Conclusion: The self-stigma formation process provides an adequate model for understanding depression self-stigma in both younger and older adults. Appropriate intervention programs aiming to reduce self-stigma should be developed, focusing on reducing the three stages of self-stigma.